O06 Clinical trial readiness and validation of onsite and remote evaluation in valosin-containing protein-associated multisystem proteinopathy: a 24-month longitudinal study - Reash, N.; Iammarino, M.; Pietruszewski, L.; Lowes, L.; Mendell, J.; Connolly, A.; Adderley, K.; Peck, N.; Peck, A.; Alfano, L. (Neuromuscular disorders : NMD, 2023)
Valosin-containing protein-associated multisystem proteinopathy (VCP-MSP), previously known as inclusion body myopathy with Paget's disease of the bone and frontotemporal dementia (IBMPFD), is a dominantly inherited, rare disorder of multisystemic involvement resulting in progressive weakness, bone disease, frontotemporal dementia, cardiac, respiratory, and/or bulbar dysfunction. Patient disease onset and presentation is heterogeneous, highlighting the need for a prospective clinical trial readiness study to inform future clinical trial design. Thirty-eight subjects (mean age: 52.5 years (range: 28-67)) with genetically confirmed VCP-MSP have enrolled with 227 visits completed to date. Visits include Baseline and 6-, 12-, 18-, and 24-month time points in a combination of in-home, remote assessments and annual visits in the standardized clinic environment. A battery of functional and patient-reported clinical outcome assessments (COA) was completed at each visit. Test-retest reliability was excellent within and between visit types (ICC≥0.8; P<0.001). Performance of most COA was the same across remote and onsite environments; two of the functional COA were slightly more variable in the home environment when compared to onsite visits, emphasizing the need for standardized equipment and furniture when implemented in clinical trials. Even though collection of the full battery of testing was limited in the home environment, reliable remote assessments allowed for continued longitudinal participation in the presence of ongoing disease progression for some patients when travel became too burdensome. Additionally, a remote-only cohort led to a broader representation of VCP-MSP, both in terms of geographic location and disease stage. Cohort level feasibility and performance of all COA, sensitivity to change and meaningful change on included assessments over 2-years will be presented.